Characterization of the bovine gene LIPE and possible influence on fatty acid composition of meat - Goszczynski, Daniel Estanislao (2014)
LIPE is an intracellular neutral lipase, which is capable of hydrolyzing a variety of esters and plays a key role in the mobilization of fatty acids from diacylglycerols. The objectives of this study were to characterize the genetic polymorphism of bovine LIPE gene and to evaluate the possible association between three SNPs in the coding regions of this gene with the fatty acid composition of meat in a cattle population. Forty-three unrelated animals from different cattle breeds were re-sequenced and 21 SNPs were detected over approximately 2600. bp, five of these SNPs were novel. Three SNPs were selected, on the basis of evolutionary conservation, to perform validation and association studies in a crossbred cattle population. Our results may suggest a possible association of SNP1 with contents of oleic acid and total monounsaturated fatty acids (p < 0.01), and SNP2 and SNP3 with Heneicosylic acid content (p < 0.01), may be helpful to improve the quality of meat and improve health.